THE IMPACT OF AUDIT COMMITTEE CHARACTERISTICS ON FINANCIAL DISTRESS - Nano Siswanto; Fuad Fuad (Diponegoro Journal of Accounting, 2017)
This study investigates the impact of audit committee characteristics on financial distress. This study uses four characteristics of audit committee. That is size of audit committee, independence of audit committee, meeting frequency of audit committee and competency of audit committee. Population used in this study is 123 servicing listed firms in Indonesia Stock Exchange in 2013-2015. Based on purposive sampling method, there are 92 samples that consist of 27 financially distressed firms and 65 non-financially distressed firms. Financial distress criteria are measured by a company that has a negative net income for two years in a row. Data are analyzed using logistic regression with SPSS 20. The results show that audit committee competence has significant negative affect with financial distress.